Recognizing and Detecting the Effectiveness of Policy Implementation Waste Management in Indonesia - Alfian Deby Artha; Heru Nurasa; Candradewini Candradewini (Universitas Teuku Umar, 2023)
The volume of waste generation in Indonesia is 65.8 million tons/year in 2018 and will continue to increase to around 70 million tons/year in 2022. To overcome this problem, the government has established several policy products, but the implementation of these policies has not been able to making Indonesia free from waste problems. This study aims to determine and detect the effectiveness of the implementation of waste management policies in Indonesia for the 2019-2022 and 2023-2025 periods. This study uses qualitative methods through a literature review approach with secondary data collection techniques. The results of the study show that (1) the implementation of waste management policies in Indonesia for the 2019-2022 period has not been effective because the targets and objectives of waste management have not been achieved, and the waste management system has not been optimal from the aspects of resources, institutions and law enforcement; and (2) the implementation of waste management policies in Indonesia in 2023-2025 is predicted and has the potential to not be effective. This is because the targets set in the regional government's RPJMD for the 2021-2026 period are much smaller than the targets set in the Jakstranas/Jakstrada. Recommendations that can be given so that the implementation of waste management policies can be more effective is to improve the regulatory system for waste management in Indonesia through harmonization between policies.